SRWC bioenergy productivity and economic feasibility on marginal lands. (1st September 2015) - Ghezehei, Solomon B.; Shifflett, Shawn D.; Hazel, Dennis W.; Nichols, Elizabeth Guthrie
Abstract: Evolving bioenergy markets necessitate consideration of marginal lands for woody biomass production worldwide particularly the southeastern U.S., a prominent wood pellet exporter to Europe. Growing short rotation woody crops (SRWCs) on marginal lands minimizes concerns about using croplands for bioenergy production and reinforces sustainability of wood supply to existing and growing global biomass markets. We estimated mean annual aboveground green biomass increments (MAIs) and assessed economic feasibility of various operationally established (0.5 ha–109 ha) SRWC stands on lands used to mitigate environmental liabilities of municipal wastewater, livestock wastewater and sludge, and subsurface contamination by petroleum and pesticides. MAIs (Mg ha −1  yr −1 ) had no consistent relationship with stand density or age. Non-irrigated Populus, Plantanus occidentalis L. and Pinus taeda L. stands produced 2.4–12.4 Mg ha −1  yr −1 . Older, irrigated Taxodium distchum L., Fraxinus pennsylvanica L., and coppiced P. occidentalis stands had higher MAIs (10.6–21.3 Mg ha −1  yr −1 ) than irrigated Liquidambar styraciflua L. and non-coppiced, irrigated P. occidentalis (8–18 Mg ha −1  yr −1 ). Natural hardwood MAIs at 20–60 years were less than hardwood and P. taeda productivities at 5–20 years. Unlike weed control, irrigation and coppicing improved managed hardwood productivity. Rotation length affected economic outcomes although the returns were poor due to high establishment and maintenance costs, low productivities and low current stumpage values, which are expected to quickly change with development of robust global markets. Highlights: SRWC productivity on operational marginal (polluted) lands was assessed. SRWCs had comparable to higher productivities versus older natural hardwood stands. Irrigation and coppicing improved SRWC productivity for some species. Rotation length affected marginal land productivity and economic outcomes.